Early Effects of Repetitive Transcranial Magnetic Stimulation Combined With Sertraline in Adolescents With First-Episode Major Depressive Disorder - Chen, Haisi; Hu, Xiwen; Gao, Jingfang; Han, Huan; Wang, Xiaole; Xue, Chuang (Frontiers in Psychiatry, 2022)
Background: Adolescence is a period of high incidence for depression. However, there is a limited treatment option for the adolescent depression. For treatment-resistant major depressive disorder, HF-rTMS of the left dorsolateral prefrontal cortex (DLPFC) appears therapeutically effective. The aim of the study is to explore the early effects of repetitive transcranial magnetic stimulation in combination with sertraline in adolescents with first-episode major depressive disorder. Methods: A total of 80 teenage patients with first-episode depression were randomly divided into the study groups．Both groups were treated with sertraline．In addition, the study group was treated with ten sessions of add-on rTMS. The control group was given sertraline only. The depressive symptom and cognitive function were assessed by the Hamilton depression rating scale 17 version (HAMD-17), Children's Depression Rating Scale-Revised (CDRS-R), Integrated visual and auditory continuous performance test (IVA-CPT) and THINC-it. Results: The total efficiency after 2 weeks of treatment in the study group was statistically significant compared to the control group (92.11% vs 71.79%，P＜0.05). The study group HAMD-17 lower than the control group, and the difference was statistically significant (Fgroup=13.245 vs 9.223,P＜0.05). Attention Quotient (listening, visual and full-scale) attention quotient of IVA-CPT in the study group [(98.24±20.72), (90.00±21.97), (94.24±21.43)] were higher than those in the control group [(82.62±27.71), (78.10±27.85), (80.21±24.47)] after treatment, and the differences were statistically significant(P＜0.05).Both two groups improved statistically significant in Spotter、Symbol Check、Codebreaker、Trails (P＜0.05)．The study group showed significantly higher score in PDQ5 after treatment(P＜0.05). Discussion: This is the most extensive blinded, randomized clinical study to date examining the efficacy of 10-Hz add-on rTMS for first-onset adolescent depression. Our results support that add-on rTMS accelerates the efficacy of the antidepressants, improving the depressive symptoms and cold cognitive function in first-episode adolescent depression. Trial registration: chictr.org.cn ChiCTR2100048534, July 10th, 2021, prospectively registered. The first veteran was enrolled July 10th, 2021. Keywords: Transcranial magnetic stimulation; Adolescent depression; Cold cognitive executive function